Differential M-ary orthogonal signaling for DS - Iossifides, A.C.
In this paper, we derive an analytical framework for the performance evaluation of an M-ary orthogonal scheme based on differential encoding/decoding of the Walsh/Hadamard chips prior/after spreading. This technique makes feasible nonpilot-assisted detection over fast fading environments such as the land mobile satellite (LMS) channel. Our results show that differential M-ary orthogonal signaling presents very good performance at Doppler frequency shifts much higher than the symbol rate. Amplitude statistics are considered to be Rayleigh, but may be easily extended to more general models based on the analytical derivation presented
Keywords: DS/CDMA land mobile satellite communications; Doppler frequency shifts; Hadamard chips; LMS channel; Rayleigh statistics; Walsh chips; Amplitude statistics; Differential M-ary orthogonal signaling; Differential decoding; Fast fading environments; Land mobile satellite channel; Nonpilot-assisted detection; Performance